APPLICATION OF THE ROLE AND FUNCTION OF NURSES IN NURSING CARE FOR ELDERLY WITH HYPERTENSION IN THE COMMUNITY (PHENOMENOLOGY STUDY) - Ninda Ayu Prabasari (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2021)
Background: The problem of hypertension in the elderly in the community, can be overcome by optimizing health services. The existence of public health center's nurses in the community cannot be ignored, at this time considered unable to display their independence as the professional. Health Center Nurse are still burdened with additional tasks that are not within the competence of the nursing profession. Role and function carried out not in accordance with the duties and authorities of nurses, have an impact on services which cannot be given optimally. Method: Research using the qualitative method with a phenomenological approach. The research objective is to obtain data by explore the application of the role and function of nurses in nursing care for the elderly with hypertension in the community. The population is all nurses who work in Jagir public health center and Pucang Sewu public health center Surabaya. Inclusion criteria are nurses have worked for at least 3 months and had made home visits for the elderly with hypertension as many as 8 participants obtained through purposive sampling. Data collection was carried out by interview and analyzed using Collaizi method. Results: obtained 8 themes, that's understanding the role and function of nurses, understanding of nursing care for the elderly with hypertension, the role and function of the dominant nurse carried out, limited services in the building, work other than roles and functions nurses, internal and external support, service quality of nurses and puskesmas, satisfaction in nurses. Conclusion: the optimal role and function of nurses in Nursing care service for the elderly with hypertension will affect the quality of service and quality of life elderly with hypertension. Recommendation: optimizing the role and function of nurses in service with a clear division of jobdisk